Groundwater nutrient loading into the northern Indian River lagoon: measurements and modeling - Al-Taliby, Wissam; Mamoua, Kamal; Pandit, Ashok; Heck, Howell; Berber, Antonio (Frontiers in Marine Science, 2023)
The Indian River Lagoon System (IRLS) has been impacted by the surrounding development, leading to excessive nutrient loads that have resulted in frequent and prolonged phytoplankton blooms in the northern reaches. Our study focused on estimating terrestrial groundwater discharge (TGD) and associated nutrient loads by combining field measurements and hydrogeologic modeling at four transects: Eau Gallie (EGT), River Walk (RWT), Banana River (BRT), and Mosquito Lagoon (MLT) across the IRLS. Multiple monitoring stations were installed to collect groundwater and surface water levels, salinity, and nutrient concentrations during 2014-2015. Samples were analyzed for dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphorus (DIP). Numerical modeling was accomplished using SEAWAT to simulate TGD rates, whereas nutrient loads were calculated by multiplying simulated TGD by measured concentrations. TGD rates and nutrient loads were also estimated specifically for the “near-shore zone” along each transect. The effect of recharge from underlying Hawthorn Formation was also evaluated by incorporating estimated recharge rates into the models. Porewater and lagoon water samples showed that ammonium predominated over (NO2+NO3) and PO4 at all sites, resulting in DIN/DIP ratio surpassing the Redfield ratio. Low nitrite/nitrate, coupled with elevated ammonium concentrations at RWT, BRT, and MLT, may be attributed to biogeochemical transformations catalyzed by mangroves and wetlands. Simulated TGD showed mild temporal but significant spatial variation, especially between EGT and RWT compared to BRT and MLT. The highest average TGD of 0.73 and 0.77 m3/d.m occurred at RWT and EGT, respectively, whereas the lowest rates were predicted at BRT and MLT. The highest estimated average DIN loads of 507 and 428 g/yr.m were received at EGT and RWT, respectively, whereas MLT and BRT exhibited lower loads. The DIP loads were remarkably lower than the DIN loads and were significantly different in space and time between sites. Elevated DIN combined with reduced DIP resulted in DIN/DIP exceeding the Redfield ratio, thereby encouraging the blooming of harmful algae. Although the majority of seepage occurs through the near-shore zone, small amounts are received along the entire transect at all sites. The Hawthorn Formation does not contribute significant recharge to the aquifer at the transect locations.